Successul negotiating Letting the other person have your way - Barnes, Ginny Pearson (New Jersey, USA Jaico publishing house, 2008)
Successful negotiation teaching you to abandon the negative myths about negotiation and learn to bulid relationships as well as get result you will be more confident and successful every time you negotiation by learning the eight essential steps of win-win negotiation and How to assess what people are thinking and what they value, and how to use these insights to get what you need while making them happy to work with you
10 12
Keywords: Communication; Comunity life; Negotiation; Sochial groups; Work invironment